The Relationship Between School Environment Factors and Students Biology Learning Outcomes - Nathania, Elga Amelinda; Mahrus, Mahrus; Merta, I Wayan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Education quality is fundamentally influenced by various factors, with the school environment playing a crucial role in shaping student learning outcomes. The school environment encompasses physical, social, and academic aspects that collectively affect students' comfort and motivation to learn. This study aims to determine the relationship between school environmental factors and biology learning outcomes of grade VII MTsN 3 Mataram students. The school environment encompasses physical, social, and academic aspects that collectively impact students' comfort and motivation to learn. This study employs a correlational, quantitative, descriptive method. The population consisted of all students of grade VII, with samples taken from grades VII-4 and VII-5 using purposive sampling techniques. Data collection techniques include questionnaires and documentation of student learning outcomes. The questionnaire instrument was validated using Aiken's V formula and tested for reliability with Cronbach's alpha, both of which yielded valid and reliable results. The normality test indicates that the data are normally distributed, and the linearity test reveals a linear relationship between the variables. Correlation analysis yielded a coefficient of r = 0.608, indicating a strong and significant relationship at a 5% significance level (r calculated exceeds the r table value). Thus, it is concluded that there is a positive and significant relationship between school environmental factors and students' biology learning outcomes. These findings can serve as input for teachers and schools in creating a supportive learning environment to enhance the educational process.